Visual communication and institutional image in the company Wcaro Consultores y Contratistas S.R.L., Moquegua 2022 - Cruz Carpio, Danna Fernanda (2024)
This research was carried out in response to the progressive competitiveness in consulting firms for the mining and construction field. The objective is to determine the relationship between visual communication and the institutional image in the company WCARO Consultores y Contratistas S.R.L., Moquegua 2022. With a basic type methodology, with a quantitative approach, observational, transversal, prospective and analytical design, at a relational level, With a population of 75 users of the company, considering a census sample, through a questionnaire, relevant results are obtained that a direct, very strong positive relationship coexists between the institutional image and the dimensions of visual communication, with a Rho of 0.855, with attention, Rho of 0.876, with perception, Rho of 0.878, with desires and Rho of 0.887 with emotion. Concluding that, there is a direct, positive and very strong correspondence (Rho=0.924) between visual communication and the institutional image in the WCARO company.